2022
DOI: 10.1037/trm0000431
|View full text |Cite
|
Sign up to set email alerts
|

Main and interactive effects of negative posttraumatic cognitions and disgust sensitivity in predicting daily experiences of sexual trauma-related mental contamination.

Abstract: Trauma-related mental contamination, or a sense of dirtiness occurring without recent contact with a contaminant, is a distressing and often persistent phenomenon after sexual trauma. Following sexual trauma, cross-sectional work has demonstrated separate positive associations between mental contamination and (a) negative posttraumatic cognitions about oneself, the world, and/or self-blame and (b) disgust sensitivity, defined as the extent to which one is prone to distress when experiencing disgust. However, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…Additionally, Olatunji et al (2008) found that maladaptive trauma-related cognitions were associated with MC in their sample and proposed that misinterpretations of the traumatic event (i.e., interpreting a sexual assault as evidence that one is tainted) lead to the development of increased MC. Moreover, Tipsword, McCann, et al (2022) demonstrated that negative trauma-related cognitions about oneself prospectively predicted increases in MC among female assault survivors. They additionally found that for women high in disgust sensitivity, negative posttraumatic cognitions about the world predicted increases in MC over time.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Additionally, Olatunji et al (2008) found that maladaptive trauma-related cognitions were associated with MC in their sample and proposed that misinterpretations of the traumatic event (i.e., interpreting a sexual assault as evidence that one is tainted) lead to the development of increased MC. Moreover, Tipsword, McCann, et al (2022) demonstrated that negative trauma-related cognitions about oneself prospectively predicted increases in MC among female assault survivors. They additionally found that for women high in disgust sensitivity, negative posttraumatic cognitions about the world predicted increases in MC over time.…”
Section: Resultsmentioning
confidence: 94%
“…Other authors have highlighted the role of posttrauma cognitive appraisals (Elliott & Radomsky, 2013; Ishikawa et al, 2013; Ojserkis et al, 2018; Olatunji et al, 2008; Tipsword, McCann, et al, 2022). Indeed, studies involving recall of past sexual assault experiences (Ishikawa et al, 2013) and analog studies involving imagining receiving a forced kiss (Elliott & Radomsky, 2013; Radomsky & Elliott, 2009) indicate that appraisals of (a) the degree of violation associated with the event, (b) responsibility for the event, and (c) the perpetrator’s morality and cleanliness are associated with MC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation